African affairs: number one - Kirkwood, Kenneth (ed.) (London, 1961)
This book cover following topics Political concepts and connotations, A note on the language of African Nationalism, The government general and political change and The Ahmadiyya movement in Nigeria. .
Keywords: Political Science